PENGENDALI KECEPATAN MOTOR DC MENGGUNAKAN SENSOR HALL BERBASIS MIKROKONTROLER ATMEGA 8535 - Roni Sinaga (Saintia Fisika, 2013)
ABSTRACT Has designed a DC motor speed control device using sensor hall based microcontroller ATMega8535. Generally, this instrument consists of a dc motor, hall sensor, microcontroller and driver. The purpose of this design is to control the speed of dc motors with pulse width control (PWM) method. The workings of this instruments is a microcontroller programmed to compare the speed of rotation of the motor is detected by the hall sensor on the motor rotation speed input. Based on the analysis of the data and obtained an error rate of 0.62% with 190rpm rotation speed up to 240 rpm. Thus, the speed of rotation of dc motor can be controlled as expected. Thus the  rotation speed control devices can be used on specific purposes, for example in the control process in the industry. Keywords : Hall Sensor, DC Motor, Mikrokontroler.